Evaluation of Trichoderma atroviride and Trichoderma longibrachiatum as biocontrol agents in controlling red pepper anthracnose in Korea - Kim, Seung Hwan; Lee, Younmi; Balaraju, Kotnala; Jeon, Yongho (Frontiers in Plant Science, 2023)
Anthracnose disease is a serious threat to red pepper crops in Korea and many other countries, causing significant reductions in yield. Currently, there are no effective control measures, except fungicide applications, which may affect consumers directly. This study aims to investigate the biological activity of Trichoderma isolates in controlling red pepper anthracnose caused by Colletotrichum acutatum in vitro and field. Out of 11 Trichoderma isolates screened for biocontrol agents against three fungal pathogens, including C. acutatum; two effective Trichoderma isolates, T. atroviride ATR697 (ATR697) and T. longibrachiatum LON701 (LON701) were selected for further investigation. Volatile organic compounds (VOCs) produced by ATR697 inhibited the mycelial growth of the C. acutatum significantly to a greater level than the isolate LON701 using the overlapping plates assay. A cellophane membrane experiment has shown that mycelial growth of C. acutatum was inhibited by 36% and 27% when treated with ATR697 and LON701, respectively. Culture filtrates (CFs) of two Trichoderma isolates inhibited the mycelial growth of C. acutatum in vitro. When red peppers were treated with spore suspensions of LON701 and ATR697, the disease severity (%) was 44.1% and 55.8%, respectively, in a curative method; while the disease severity (%) was 5% and 11.6%, in LON701- and ATR697-treated red peppers, respectively, in a preventive method. These results showed the suppression of disease severity (%) was relatively higher in the preventive method than in the curative method. Furthermore, Trichoderma isolates, ATR697 and LON701 were resistant to commercial chemical fungicides in vitro, indicating these strains may also be used synergistically with chemical fungicide (pyraclostrobin) against the growth of C. acutatum. There was no difference in the inhibition rate (%) of the pathogen between the treatment with LON701 alone and LON701+pyraclostrobin. Based on in vitro results, ATR697 and LON701 played a role to control red pepper anthracnose effectively in field conditions, with a disease rate of 14% in LON701 treatment, when compared to ATR697, chemical and non-treated controls. Overall, our study showed the ability of Trichoderma isolates in controlling red pepper anthracnose and their potential to develop as novel biocontrol agents to replace chemical fungicides for eco-friendly sustainable agriculture.